Sawmill Residue Valorization as Adsorbent for Cd2+ from Aqueous Solution - Ali El-Rayyes; Ibrahim Arogundade; Ezekiel Folorunsho Sodiya; Edwin Andrew Ofudje; Moamen S. Refat,; Amnah Mohammed Alsuhaibani; James Asamu Akande (BioResources)
Raw sawmill wood adsorbent (RSWA) and sawmill wood biochar adsorbent (SWBA) were evaluated as eco-friendly materials for removing cadmium ions (Cd²⁺) from aqueous solutions. The sawmill waste was thermally treated, and the resulting biochar was characterized using FT-IR, SEM, and BET analyses, revealing a rough, porous structure comprising functional groups that enhance adsorption. Batch adsorption experiments demonstrated that SWBA exhibited a higher adsorption capacity (85.4 mg/g at 45 °C) compared to RSWA (78.6 mg/g at 40 °C), with equilibrium times of 180 min for SWBA and 150 min for RSWA. Adsorption efficiency was pH-dependent, with optimal removal occurring at pH 6 for SWBA and pH 5 for RSWA. Kinetic modeling confirmed that adsorption followed the pseudo-second-order model, while isotherm studies indicated a stronger correlation with the Freundlich model. Thermodynamic analysis confirmed the process to be endothermic and spontaneous. Desorption studies revealed a decline in adsorption efficiency over multiple cycles, with RSWA exhibiting slightly better desorption performance than SWBA. These findings highlight sawmill wood biochar as a cost-effective and sustainable solution for wastewater treatment, particularly in heavy metal removal.